EFEKTIFITAS KARBON AKTIF DALAM MENURUNKAN KADAR BILANGAN PEROKSIDA DAN PENJERNIHAN WARNA PADA MINYAK GORENG BEKAS - Windy Utari; Dr. dr. Wirsal Hasan, MPH; dr. Surya Dharma, MPH (Lingkungan dan Kesehatan Kerja, 2014)
The effectiveness of activated carbon in decreasing the peroxide levels and purification colors on used cooking oil. The need of cooking oil is increase. Because of the price of cooking oil is relative expensive and the urgency of economic, unwittingly, people often consume the used cooking oil that contains high levels of peroxide continuously. Activated carbon is an adsorbent that is used to process the used cooking oil. The purpose of this research is to determine effectiveness of activated carbon in decreasing peroxide levels in the used cooking oil. The type of research is Quasy Experiment with Pre and Post Test Design. The used cooking oil as control was not given the activated carbon and the other mixed 1 gr, 2 gr and 3 gr of the activated carbon into every 100 grams used cooking oil. Each done three times. The result of research showed that peroxide levels of the used cooking oil without being mixed the activated carbon is 12,0 meq/kg with the yellow brown color. Peroxide levels of each activated carbon 1 gr, 2 gr, and 3 gr were 5,4 meq/kg, 1,1 meq/kg, and 1,2 meq/kg with the yellow golden color, while according to Departemen Perindustrian SNI 3741-1995, the peroxide levels that permitted is 2 meq/kg. Based of Anova One-Way, the result showed there were significant differences between various treatment of the activated carbon to decrease peroxide levels in the used cooking oil. BNT test result showed that 2 gr activated carbon is the most effective to decrease peroxide levels in the used cooking oil. Suggested to the people especially to fried merchant or for another food that is processed using cooking oil as an intermediary, to use 2 gr activated carbon to every 100 grams the used cooking oil. Keyword : used cooking oil, activated carbon, peroxide concentration, purification color.